2022
DOI: 10.3390/pr10010166
|View full text |Cite
|
Sign up to set email alerts
|

(S)-5-Methylmellein Isolated from an Endogenous Lichen Fungus Rosellinia corticium as a Potent Inhibitor of Human Monoamine Oxidase A

Abstract: In this study, the inhibitory activities against human monoamine oxidases (hMAOs) were evaluated using a library of 195 endogenous lichen fungi from Ukraine. Among them, the extract ELF68 of the endogenous fungus Rosellinia corticium from the lichen Pseudevernia furfuracea (L.) Zopf. exhibited the strongest inhibitory activity against hMAO-A. Using the activity-guided method, (S)-5-methylmellein (5MM) was isolated from the extract and had an IC50 value of 5.31 µM for hMAO-A with a lower potency for hMAO-B (IC5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 51 publications
0
5
0
Order By: Relevance
“…Another small polyketide, (S)-5-methymellein 156, a small lactone isolated from the endogenous fungus Rosellinia corticium within the lichen Pseudevernia furfuracea, exhibited MAO inhibition. Compound 156 was identified through bioassay guided fractionation and exhibited IC50 values of 5.31 and 9.15 μM for human MAO-A and MAO-B, respectively [196]. Its enantiomer, (R)-5-methylmellein 157, was also isolated from the fermented mycelia of Xylaria nigripes, and 157 showed moderate selectivity toward MAO-A with IC50 values of 4.6 and 38.5 μM for human MAO-A and MAO-B, respectively [197].…”
Section: Mao Inhibitors From Miscellaneous Classes Of Natural Productsmentioning
confidence: 99%
See 1 more Smart Citation
“…Another small polyketide, (S)-5-methymellein 156, a small lactone isolated from the endogenous fungus Rosellinia corticium within the lichen Pseudevernia furfuracea, exhibited MAO inhibition. Compound 156 was identified through bioassay guided fractionation and exhibited IC50 values of 5.31 and 9.15 μM for human MAO-A and MAO-B, respectively [196]. Its enantiomer, (R)-5-methylmellein 157, was also isolated from the fermented mycelia of Xylaria nigripes, and 157 showed moderate selectivity toward MAO-A with IC50 values of 4.6 and 38.5 μM for human MAO-A and MAO-B, respectively [197].…”
Section: Mao Inhibitors From Miscellaneous Classes Of Natural Productsmentioning
confidence: 99%
“…Figure 15 shows the structures and Table 7 presents the IC50 values of selected miscellaneous natural product classes on natural product inhibitors. 196] Note: natural products tested on total MAO are not listed. Enzyme source: F = recombinant human MAO-A and -B.…”
Section: Mao Inhibitors From Miscellaneous Classes Of Natural Productsmentioning
confidence: 99%
“…5B). In previous studies, most of MAO inhibitors were reported as competitive inhibitors [27][28][29][30]32,33], and ChE inhibitors were reported as mixed-type inhibitors [22][23][24]. These results suggested that compound 1 was a competitive MAO-B inhibitor and a mixed-type BChE inhibitor.…”
Section: Enzyme Kineticsmentioning
confidence: 87%
“…However, compound 1 showed weak inhibitory activity against BACE1 as well as MAO-A and AChE. Compared with other natural inhibitors, MAO-B inhibitory activity of compound 1 was similar or higher than 5MM (IC 50 =9.15 μM) [29], alternariol (AT, IC 50 =20.7 μM) [28], glycyrol (GC, IC 50 =29.48 μM) [40] and chromenone derivative 1 (IC 50 =27.0 μM) [30], but lower than chromenone derivative 2 (IC 50 =3.42 μM) [30], and liquiritigenin (IC 50 =0.098 μM) [40]. In addition, BChE inhibitory activity of compound 1 was slightly lower than GC (IC 50 =7.22 μM) [40].…”
Section: Inhibition Studies Of Mao-a and Mao-bmentioning
confidence: 88%
See 1 more Smart Citation